Stilistika dalam Geguritan Kidung Wengi Karya Hadi Pamungkas - Khaeroni, Qurrota A'yuna (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
This writing is intended to investigate the style of the language contained in the geguritan Kidung Wengi by Hadi Pamungkas using a stylistic scalpel. This writing uses a research lens that focuses on the object of study regarding the style of language, imagery, and typography used. The method used by the author in examining this geguritan is to use a qualitative descriptive method with the technique of collecting physical evidence in the form of words, phrases, and sentences in the geguritan containing the focus of the writing objective. Based on the research that has been done, the results obtained in the form of finding figure of speech, imagery, diction, and typography that are used to describe a situation as well as tools to beautify the language of geguritan. In this geguritan found images such as visual images, auditory images, motion images, and tactile images. There are also figures of speech found in Kidung Wengi's geguritan, including personification, metaphor, and hyperbole. This Gegutitan also contains dictions in its writing. In addition, in writing this geguritan the author also includes typography which is a writing technique related to the use of writing rules and the use of punctuation marks.